From science to faith through superstition, and vice versa: Philology, alchemy and Kabbalah in the works of Blaise de Vigenère - Popović Dušan (Belgrade Philosophical Annual, 2024)
Taking into account all the original and translational works of one of the most significant writers of the French Renaissance, it is the opinion of the author of this paper that a more accurate analysis of de Vigenère's viewpoints would be productive and could contribute to understanding even better and in more detail the positions that humanists took on science, faith and superstition. Although his greatest merits belong to the domain of the translations of Roman and Byzantine historians in the first place, nevertheless de Vigenère's original contributions to the history of ideas in the Renaissance, which derive from the prefaces to and commentaries on the published translations, remained considerably in the shadow, as was also the case of two of his entirely original publications, namely the Essay on Codes and the Essay on Fire and Salt. While in the second work the subject matter is predominantly alchemy, the first piece of writing especially deals with the subject that the author assigns himself the task to promote, i.e. the creation of a universal religion for all the peoples of the world, established upon an esoteric and Kabbalist interpretation of the Scriptures and other Christian dogmas. Such a holistic approach (having its roots mostly in a late antique, Neoplatonist milieu) is based on the application of the occult knowledge appertaining to mythology, religious syncretism and Kabbalah, but is also founded on the aspirations of the Jesuits, who were striving to convert recently discovered "heathen" peoples using local languages and writing systems.